TINJAUAN YURIDIS KEDUDUKAN HUKUM PARA PIHAK DALAM PERJANJIAN TERAPEUTIK - Evy Savitri Gani (IAIN Ambon, 2018)
This paper examines the legal status of the parties to the therapeutic agreement. The problem in this paper is how the legal status of the parties to the treaty is therapeutic and what is the legal protection for the patient in the therapeutic covenant. Data were collected through review of laws, books or literature and analyzed descriptively qualitatively. The results showed that the position of the parties between patients and doctors according to law equal or balanced. This is reflected in the rights and obligations set forth in the legislation in the field of health. While the form of legal protection is also reflected in Law Number 36 Year 2009 on Health, Law Number 29 Year 2004 About Medical Practice and Law Number 8 Year 1999 About Consumer Protection.